Does a new knee design perform as well asthe design it replaces?. Issue 12 (December 2012) - Molt, M.; Ljung, P.; Toksvig-Larsen, S.
Abstract : Objectives: The objective of this study was to compare the early migration characteristics and functional outcome of the Triathlon cemented knee prosthesis with its predecessor, the Duracon cemented knee prosthesis (both Stryker). Methods: A total 60 patients were prospectively randomised and tibial component migration was measured by radiostereometric analysis (RSA) at three months, one year and two years; clinical outcome was measured by the American Knee Society score and the Knee Osteoarthritis and Injury Outcome Score. Results: There were no statistically significant differences in rotation or translation around or along the three coordinal axes, or in the maximum total point motion (MTPM) during the two-year follow-up. Conclusions: The Triathlon cemented knee prosthesis has similar early stability and is likely to perform at least as well as the Duracon cemented knee prosthesis over the longer term.